FUZZY LOGIC BASED INDIRECT VECTOR CONTROL OF SQUIRREL CAGE INDUCTION MOTOR - Nur, Ahmet; Omac, Zeki; Oksuztepe, Eyyup (Yildiz Technical Univ, 2017)
Squirrel cage induction motors are widely used in industry. These induction motors need smart control applications for high performance. In this paper an indirect vector control of squirrel cage induction motor is modelled mathematically. The mathematical model is moved to simulation using Matlab/Simulink software. For improvement, the indirect vector control simulation is based on fuzzy logic. Eventually, the simulation results for fuzzy logic speed control of induction motor are obtained for different reference speeds. The results showed effectiveness of fuzzy control system for indirect vector control of squirrel cage induction motor simulation model.
Keywords: Squirrel cage; induction motor; indirect vector control; fuzzy logic